2021
DOI: 10.2147/opth.s299141
|View full text |Cite
|
Sign up to set email alerts
|

Management of Persistent Corneal Epithelial Defects with Human Amniotic Membrane-derived Dry Matrix

Abstract: Objective To report the outcomes of using human amniotic membrane-derived dry matrix (AMDDM) in the management of persistent corneal epithelial defects (PEDs) of various etiologies. Methods A cohort study of 84 patients age range 7 to 92 years with 93 PEDs were treated with AMDDM (Omnigen ® using OmniLenz ® at two centers (Queen Victoria Hospital and Maidstone Hospital) in the UK. The main outcome measures were heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…19 Maqsood et al reported the results of Omnigen (NuVision Biotherapies Ltd, Nottingham, United Kingdom), which is a dehydrated AM applied under a BCL (OmniLenz; NuVision Biotherapies Limited), in the management of persistent corneal epithelial defects of various etiologies. 14 They reported that 58% of the eyes showed complete healing and 28% showed partial decrease in size of PEDs with average treatment length recorded as 22.4612.3 days. 14 Our results showed similar healing rates as those reported in the studies by Mimouni et al and Maqsood et al In this study, 72.7% of the eyes healed completely after placement of a single graft, and 100% eyes healed after two grafts and remained free of epithelial defects for a mean of 7.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Maqsood et al reported the results of Omnigen (NuVision Biotherapies Ltd, Nottingham, United Kingdom), which is a dehydrated AM applied under a BCL (OmniLenz; NuVision Biotherapies Limited), in the management of persistent corneal epithelial defects of various etiologies. 14 They reported that 58% of the eyes showed complete healing and 28% showed partial decrease in size of PEDs with average treatment length recorded as 22.4612.3 days. 14 Our results showed similar healing rates as those reported in the studies by Mimouni et al and Maqsood et al In this study, 72.7% of the eyes healed completely after placement of a single graft, and 100% eyes healed after two grafts and remained free of epithelial defects for a mean of 7.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, commercially available dehydrated amnion tissue has been introduced, which can be easily stored and transported at room temperature. 14…”
mentioning
confidence: 99%
“…Patients were divided according to the cause of persistent corneal ulcer into four groups: group I, including 14 eyes with aqueous tear-deficient dry eye; group II, including six eyes post-keratoplasty (four eyes postpenetrating keratoplasty and two eyes post-deep anterior lamellar keratoplasty); group III, including four eyes with corneal chemical burn (three eyes with alkaline chemical burn and one eye with acidic chemical burn); and group IV, including 16 eyes with persistent corneal ulcer due to other causes, including post-fungal keratitis (Aspergillus fumigatus and Candida albicans), post-coronavirus disease (an episode of severe coronavirus disease and admission to the intensive care unit due to coronavirus disease-induced respiratory failure), post-cataract surgery, post-herpes simplex virus keratitis, limbal stem cell deficiency, corneal ulceration due to radiotherapy, and neurotrophic keratitis ( 191 persistent corneal ulcer was defined as a corneal epithelial defect with / without stromal defect persisting for at least 2 weeks without improvement in the size or depth despite standard treatment [16].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many techniques have been developed to preserve most of the biological properties of amniotic membranes by storage techniques and to prevent disease transmission to recipients [ 204 , 205 , 206 ]. In 2021, a cohort study from Queen Victoria Hospital and Maidstone Hospital showed that a dry and stable human amniotic membrane-derived matrix, Omnigen ® using OmniLenz ® (NuVision Therapies, Nottingham, UK), can easily be applied in the clinical setting with biochemical stability and efficiency as a novel tool to treat LSCD [ 207 , 208 ]. Based on the technique of dried amniotic membrane, Ting et al developed a modified ACER method by using low-temperature vacuum-dehydrated amniotic membrane instead of the cryopreserved amniotic membrane and fibrin glue rather than sutures [ 206 , 209 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%